MoO3/SiO2-ZrO2 Catalyst: Eeffect of Calcination Temperature on Physico-chemical Properties and Activities in Nitration of Toluene - Sunil M. Kemdeo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2012)
12 wt % molybdena was deposited over 1:1 silica zirconia mixed oxide support and the resultant catalyst was calcined between the 500 to 700 oC range of temperature. The samples were characterized by XRD, FT-IR, BET, SEM, NH3-TPD and pyridine adsorbed FT-IR techniques. Nitration of toluene was studied as a model reaction over the prepared catalysts and parameters like effect of reaction temperature, effect of various solvents, catalyst reusability are studied. It was found that conversion of toluene varies with the presence of Brönsted acid sites over the catalyst surface and para-nitrotoulene selectivity is associated with pore size of the catalyst. Over the same catalysts, nitration was extended for some other aromatics. Avoid of sulfuric acid in the present process is an interesting concern in view of green chemistry. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)